Formulation and Evaluation of Orally Disintegrating Taste Masked Gemifloxacin Mesylate Tablet - Dr. Sangeeta Asija; Srishti Jain; Dr. Rajesh Asija; Anil Kumar Goyal; Jitendra Kumar (International Journal of Allied Medical Sciences and Clinical Research, 2021)
Gemifloxacin is a broad spectrum antibacterial agent active against gram positive and gram negative organism. It is very bitter in taste. In the present work an attempt has been made to develop orally disintegrating taste masked tablet of Gemifloxacin using ion exchangeresins (Amberlite IRP 88) as a taste masking agent. Different drug: resin ratios were tried to prepare taste maskedcomplex. FT-IR spectroscopy and differential scanning calorimetry were used to investigate the physical characteristics of the complex. Tablets were prepared by direct compression technique using two super disintegrants viz.cross povidone and sodium starch glycolate. Tablets of all batches were tested for various evaluation parameters. Tablets formulated with10% Crosspovidone (GRT05) showed lowest wetting time (16 sec). The % cumulative release of drug from tablet (GRT05) was found to be more than 99% within 40mins. It was thus possible to formulate Orally disintegrating tablets of Gemifloxacin using simple and cost effective, Ion Exchange Resin Complexation technique.